2018
DOI: 10.1002/da.22731
|View full text |Cite
|
Sign up to set email alerts
|

In rape trauma PTSD, patient characteristics indicate which trauma-focused treatment they are most likely to complete

Abstract: Individual differences among patients affect the likelihood they will complete a particular treatment, and clinicians can consider these moderators in treatment planning. In the future, treatment selection models could be used to increase the percentage of patients who will receive a full course of treatment, but replication and extension of such models, and consideration of how best to integrate them into routine practice, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 53 publications
1
25
0
2
Order By: Relevance
“…Following (Keefe et al, 2018;, two machine learning techniques were used to select pre-treatment variables in each dataset to build a treatment-modality interaction PAI model. Although the STEPd dataset was used before to develop a PAI model (Huibers et al, 2015), in that study less advanced methods were applied to build a prediction model (i.e., no imputation of missing data, stepwise variable selection approach and leave-one-out cross validation).…”
Section: Transformation Of the Outcome Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Following (Keefe et al, 2018;, two machine learning techniques were used to select pre-treatment variables in each dataset to build a treatment-modality interaction PAI model. Although the STEPd dataset was used before to develop a PAI model (Huibers et al, 2015), in that study less advanced methods were applied to build a prediction model (i.e., no imputation of missing data, stepwise variable selection approach and leave-one-out cross validation).…”
Section: Transformation Of the Outcome Variablementioning
confidence: 99%
“…Similar studies have been conducted since, investigating individual advantages in CBT versus IPT for MDD (Huibers et al, 2015), CBT versus psychodynamic treatment for MDD (Cohen et al, 2019), and CBT versus CBT with integrated exposure and emotionfocused elements for MDD (Friedl et al, 2020). The PAI has also been studied in the contexts of supportive-expressive therapy, antidepressants and placebo for MDD (Zilcha-Mano et al, 2016), eye movement desensitization and reprocessing versus cognitive therapy for posttraumatic stress disorder (PTSD, Deisenhofer et al, 2018), prolonged exposure versus cognitive processing therapy for PTSD (Keefe et al, 2018), antidepressants versus placebo for MDD (Webb et al, 2019), and CBT versus a positive psychology intervention for MDD (Lopez-Gomez et al, 2019). Overall, these studies indicated that different treatments may have different clinically relevant effects for a given individual, and that use of the PAI may improve outcomes by optimizing treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…To construct a powerful prediction algorithm, we used two techniques to identify predictors for long-term depression severity from the 29 variables available: a model-based recursive partitioning method followed by bootstrap resampling in conjunction with backwards elimination (R packages "mobForest" and "bootstepAIC," Rizopoulos & Rizopoulos, 2009; prevous applications of this method: Keefe et al, 2018;Zilcha-Mano et al, 2016). The modelbased recursive partitioning technique is based on a random forest algorithm .…”
Section: Variable Selectionmentioning
confidence: 99%
“…More symptomatic veterans appear to be at increased risk of premature termination, consistent what has been observed in outpatient populations. Future studies should qualitatively investigate veterans’ reasons for treatment dropout, examine the role of medication usage and compliance, determine symptom changes across the course of treatment and how they relate to program completion, and examine moderators of treatment completion (e.g., Keefe et al, 2018) and receipt of TFPs in order to enhance treatment completion and outcome.…”
Section: Discussionmentioning
confidence: 99%